2008
DOI: 10.4028/www.scientific.net/amm.13-14.99
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties for Quantitative Thermoelastic Stress Analysis of Composite Structures

Abstract: Abstract. The sensitivity of the thermoelastic response to variations in the fibre volume fraction, resin material and manufacturing route is assessed. To quantify any effects a comprehensive materials testing programme has been conducted to obtain coefficients of thermal expansion, specific heat, density and the elastic properties, which is described in detail in the paper. The work is focused on attempting to ascertain if the source of the response is from the isotropic resin rich layer or from the orthotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The frequency and temperature dependence of the matrix was explicitly modelled by providing frequency-and temperature-dependent modulus and loss factors, according to the measurements in based on literature [49,50] and was assumed to be independent of temperature and frequency for the given testing range. To determine the sensitivity of the numerical macroscopic predictions on the assumption of constant matrix Poisson's ratio, we performed two simulations on the same microstructure considering two 'extreme' values of matrix Poisson's ratio of 0.32 and 0.45, at 25 °C.…”
Section: mentioning
confidence: 99%
“…The frequency and temperature dependence of the matrix was explicitly modelled by providing frequency-and temperature-dependent modulus and loss factors, according to the measurements in based on literature [49,50] and was assumed to be independent of temperature and frequency for the given testing range. To determine the sensitivity of the numerical macroscopic predictions on the assumption of constant matrix Poisson's ratio, we performed two simulations on the same microstructure considering two 'extreme' values of matrix Poisson's ratio of 0.32 and 0.45, at 25 °C.…”
Section: mentioning
confidence: 99%
“…Fruehmann et al [11] showed that variations in fibre volume fraction have significant influence on the thermoelastic response from polymer composite materials, and likewise in [12] demonstrated the sensitivity to variations on the fibre volume fraction, resin material and manufacturing methods of glass/epoxy composites. Only one publication [7] thus far has considered the paint coating that is used in TSA to create a uniform and enhanced surface emissivity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the decades since the publication of [4], there have been many publications, e.g. [5][6][7][8][9][10][11][12][13][14], attempting to interpret the thermoelastic response from laminated polymer composite materials. Zhang et al [5] studied unidirectional (UD) carbon/epoxy composites and determined that the thermoelastic response became independent of the surface ply for resin-rich surface layers in excess of 30 µm in thickness.…”
Section: Introductionmentioning
confidence: 99%
“…[15] derived a strain‐based analytical model equivalent to and tested it under axial strain control on GRP tensile coupons with different lay‐ups. Their study also reported a tendency of experimental results to better conform to the predictions of the strain witness model, although the same authors have recently added that these evaluations are strongly dependent on the level of accuracy of the material data properties employed in the models [16].…”
Section: Introductionmentioning
confidence: 99%